CORPORATE RESPONSIBILITY AND CORPORATE RESILIENCE IN INDONESIA - AT THE BEGINNING OF THE COVID PANDEMIC - Regina Jansen Arsjah; Juwita Tanamal; Harti Budi Yanti (Media Riset Akuntansi, Auditing & Informasi, 2023)
This study examines the effect of corporate social responsibility in terms of corporate responsibility to shareholders, employees, suppliers, customers and consumers, the environment, and society on corporate resilience during the Covid-19 crisis. Resilience has stability and flexibility dimensions. The focus of this research is on the flexibility dimension. This quantitative study used data from 2020 when the Covid-19 outbreak began in Indonesia. One hundred four non-financial companies listed on the Indonesia Stock Exchange were selected as samples for this study. The results showed that the company's responsibility to the environment and society positively affected corporate resilience. The company's responsibility to suppliers, customers, and consumers has a negative effect on corporate resilience. Meanwhile, the company's responsibility to shareholders and employees does not affect corporate resilience. The results show that not all aspects of corporate social responsibility affect corporate resilience during the first year of the Covid-19 crisis.